The cytoskeleton of digitonin-treated rat hepatocytes. - Fiskum, G (1980)
Treatment of isolated rat hepatocptes with low concentrations of digitonin increases the permeability of the plsma membrane to cytosolic proteins without causing release of organelles such as mitochondria into the surrounding medium. Electron microscopy showed that treatment of the cells with increasing concentations of digitonin results in a progressive loss in the continuity of the plasma membrane, while most other aspects of cellular morphology remain normal. Depletion of background staining material from the cytosol by digitonin treatment of the cells greatly enhances the visualization of the cytoskeleton. The use of this technique, together with immunofluorescent light microscopy, has verified the presence of an actin-containing filamentous network at the hepatocyte cortex as well as intermediate filaments distributed throughout the cell. Digitonin is thus useful both for selectively permeabilizing the plasma membrane and for intensifying the appearance of intracellular structures such as microfilaments that are normally difficult to observe in cells such as hepatocytes.